Angiomatoid fibrosis histiocytoma in the pulmonary artery: A case report. Issue 9 (13th March 2021) - Mishima, Shuji; Mishima, Osamu; Azuhata, Koji; Shimojo, Hisashi; Ito, Nobuo; Misawa, Kenji; Shimizu, Kimihiro
Abstract: Angiomatoid fibrosis histiocytoma (AFH) is a rare neoplastic disease. Only one report has demonstrated an intraluminal tumor of the pulmonary artery (PA) corresponding to AFH to date. We describe the case of AFH with EWSR1‐CREB1 fusion occurring in the ascending artery. A 42‐year‐old man exhibited an abnormal nodule on chest computed tomography (CT) during checkup. It revealed an intraluminal mass in the ascending artery with significant metabolic uptake in positron emission tomography (PET)/CT. Therefore, right upper lobectomy with wedge resection of the PA trunk was performed. Histologically, the tumor was multinodular and surrounded by a dense lymphoplasmacytic cuff. Each nodule was composed of myxoid stroma and comprised ovoid or spindle cell fascicles with mild atypia. Fluorescent in situ hybridization (FISH) analysis confirmed EWSR1‐CREB1 fusion. A diagnosed as AFH was made. This report widens the spectrum of differential diagnoses of primary tumors occurring in the PA. Abstract : Angiomatoid fibrosis histiocytoma (AFH) is a rare neoplastic disease. Only one report has demonstrated an intraluminal tumor of the pulmonary artery trunk corresponding to AFH with ESWR1‐ATF1 fusion to date. This is the first reported case of AFH occurring in the ascending artery with EWSR1‐CREB1 fusion.